Tribute to the legend Mr. veterinary public health, Professor James Steele (1913 -2013): a late pioneer of one health in Nigeria (2014)
Between 2013 and 2014, the One Health World witnessed the demise of three pioneers of One Health in Nigeria- Professor Gabriel Oluwole Esuruoso, the Father of Veterinary Public Health in Nigeria, who died on 26lh January 2013 aged 80; Prof James Steele, often referred to as the “father of veterinary public health”, died Nov. 10 2013, aged 100 years old; and Prof David Goldsmith Montefiore who passed away on June 10 2014. aged 85. Nigeria was opportuned to have the One Health input of Prof James Steele known as “Mr. Veterinary Public Health’and acclaimed Father of Veterinary Public Health'. "Father of One Medicine" and founder and advocate of One World. One Health. One Medicine, who was invited in 1978 as Visiting Professor and External Examiner to the Department of Veterinary Public Health and Preventive Medicine by the Founding Head of Department. Prof G.O. Esuruoso, one of the earliest pioneers of One Health in Nigeria. The author was also destined during his Sabbatical Leave to have an interactive interview session with Prof James Steele after attending the 20th Annual James Steele lecture/ 99th birthday Dinner of Professor James Steele 4th and 6th April 2012 at the Texas School of Public Health, Houston. Texas. USA. The interview session was facilitated by a long time American veterinary epidemiology colleague and professional friend. Dr. Peter Cowen, a University of Ibadan 1978 DVM graduate. This article is a tribute to the memory of the late Prof James Steele for his contribution to the history of One Health in Nigeria, and shares his (and others’) perspectives on challenges and factors to hasten One Health in Nigeria.